Prevalence and associated risk factors of chlamydia trachomatis among gynecology clinic attendees in a tertiary institution in Ogun State, Nigeria. (2019)
Chlamydia trachomatis is one of the most prevalent bacterial causing urogenital infections in men and women worldwide. There have been increasing reports of the prevalence of C. trachomatis in Nigeria. Aims: This study aimed to detect the prevalence of C. trachomatis seromarkers immunoglobulin G (IgG) and immunoglobulin A (IgA) and also to determine their associated risk factors among gynecology clinic attendees in the Babcock University Teaching Hospital, Ilishan Remo, Ogun State of Nigeria. Materials and Methods: This was a cross sectional study involving 145 consenting attendees of gynecology clinic of the hospital. Blood samples were collected and tested for =C. trachomatis IgG and IgA using the enzyme linked immunosorbent assay technique. Sociodemographic and sex behavioral factors were obtained by the interviewer based questionnaires, whereas statistical analysis was done using SPSS version 23. Results: Overall prevalence of combined IgG and IgA was 46 (31.7%). Among the infected, 30 (65.2%) were young women aged 15–25 years and majority, 109 (75%), had never used condom while 83 (57.2%) had only one sex partner in the preceding 3 months. Twenty three (15.9%) had a positive history of sexually transmitted infection (STIs), whereas 75 (51.7%) had ≥2 lifetime sex partners. Factors associated with the occurrence of both seromarkers on bivariate analysis included the previous history of STI and number of lifetime sex partners (P < 0.05), but with further analysis, only lifetime sex partners remained statistically significant (odds ratio = 5.63, confidence interval = 1.09–29.05, P = 0.007). Conclusion: There was a high prevalence of active, chronic, and persistent C. trachomatis infection with number of lifetime sex partner being a significant risk factor among our clinic attendees in Ogun State. Appropriate sex education should be encouraged among young people to reduce the burden of the infection and its attendant sequelae in our community.